IFPA meeting 2015 workshop report II: mechanistic role of the placenta in fetal programming; biomarkers of placental function and complications of pregnancy. (December 2016) - Andraweera, P.H.; Bobek, G.; Bowen, C.; Burton, G.J.; Correa Frigerio, P.; Chaparro, A.; Dickinson, H.; Duncombe, G.; Hyett, J.; Illanes, S.E.; Johnstone, E.; Kumar, S.; et al.
Abstract: Workshops are an integral component of the annual International Federation of Placenta Association (IFPA) meeting, allowing for networking and focused discussion related to specialized topics on the placenta. At the 2015 IFPA meeting (Brisbane, Australia) twelve themed workshops were held, three of which are summarized in this report. These workshops focused on various aspects of placental function, particularly in cases of placenta-mediated disease. Collectively, these inter-connected workshops highlighted the role of the placenta in fetal programming, the use of various biomarkers to monitor placental function across pregnancy, and the clinical impact of novel diagnostic and surveillance modalities in instances of late onset fetal growth restriction (FGR).